Raman micro-Spectroscopy application for studying of the components of Cytoplasm bovine oocytes matured in vitro - Jimenez, Luis Emanuel (2016)
The process of in vitro oocyte maturation, both at nuclear and cytoplasmic level, is a crucial stage to the success of subsequent events, such as the in vitro fertilization and the early embryonic development. During this process an increase and redistribution of organelles occurs which leads to higher lipid and glutation contents. In addition, the biochemical profile of the cytoplasm experiences significant changes, mainly due to the increase in transcription and the consequent protein synthesis. The necessary energy for these events is provided by an increased glycolysis (1).The aim of this work is to characterize the chemical composition of the cytoplasm of in vitro matured bovine oocytes (IVM) by using Raman microscopy. We focus on the spectral behavior of characteristic bands of DNA, RNA, proteins, carbohydrates and lipids.The Raman spectra were acquired from five different points of the cytoplasm of each whole oocyte (n=16). In order to minimize the contribution from the molecules of the Zona Pellucida (ZP), the ZP spectrum was subtracted from the cytoplasm spectra. The vibrational characterization of the ZP glycoproteins has been previously performed by our group (2). We used the band corresponding to the vibration of sialic acid, component of the ZP glycoproteins, as a reference for the spectral subtraction. The resulting spectra show high phospholipid content and a significant absence ofsugar bands in the IVM cytoplasm. These results are in accordance with the vesicle formation and the expenditure of energy reserves that led to the matured oocyte status.